1996
DOI: 10.1590/s0037-86821996000500005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência dos marcadores sorológicos dos vírus da hepatite B e D em crianças das tribos Caiabietxucarramãe do parque indígena do Xingu, Brasil central

Abstract: The medical literature has shown that the inhabitants of the Amazon region are highly affected by hepatitis B and delta viruses infection, but this has never been studied in Indian children by age group. A study of the prevalence of serological markers of hepatitis B and delta viruses in Indian children aged 0 to 14 years living in the PIX was carried out. This Park is located in Central Brazil, a region which is in the transition between the savannab to the south and the Amazon jungle to the north. To determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
0
15
0
9
Order By: Relevance
“…In fact, the Waorani have the highest HBV prevalence of any Amazonian group investigated to date. [1][2][3][4][7][8][9] Many investigators have sought to determine the modes of transmission of HBV, particularly in populations where it is hyperendemic. Vertical (perinatal) transmission alone would not be adequate to produce the high prevalence of HBV infection seen among the Waorani, since only 11% of reproductive age women appear to be carriers of the virus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the Waorani have the highest HBV prevalence of any Amazonian group investigated to date. [1][2][3][4][7][8][9] Many investigators have sought to determine the modes of transmission of HBV, particularly in populations where it is hyperendemic. Vertical (perinatal) transmission alone would not be adequate to produce the high prevalence of HBV infection seen among the Waorani, since only 11% of reproductive age women appear to be carriers of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also found a high prevalence of HBV infection in young children in Amazonian populations where the disease is hyperendemic. 1,4,[8][9][10]13,20,21 Several alternative hypotheses have been proposed to explain the efficient horizontal transmission of HBV and HDV in hyperendemic populations. These include contact with infected skin lesions; 22-24 insect vectors; [24][25][26][27][28][29][30][31] cultural practices that involve puncturing or cutting the skin, receiving injections, the sharing of beds, razors or other personal items; 1,2,31 dental care; 2,32,33 and household contact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(27) Cross-sectional study (descriptive) Studies the prevalence of serological markers of hepatitis B and delta in indigenous children from 0 to 14 years living in the Xingu Indigenous Park. (28) Cross-sectional study (descriptive) Identifies epidemiological patterns and risk factors for HBV and HDV infections in Barcelos, at the Rio Negro basin, Amazon region. …”
Section: Methodsmentioning
confidence: 99%